PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI FRONTLINER, (Studi pada Cabang Bank Kalsel yang berada di Wilayah Banjarmasin) - Rina Armiaty; zakhyadi Ariffin (JWM (JURNAL WAWASAN MANAJEMEN), 2014)
The purpose of this study is to investigate and analyze the influence of organizational culture on employee performance and motivation of employees especially front-liner. The unit of analysis in this study is the front-liner employees in branch office environments Banjarmasin South Kalimantan region. Respondents used at this research as 58 employees, by census sampling technique. Measurement variables using Likert scale, and use analysis multiple linear regression with SPSS. The results show organizational culture variables positive and significant effect on the performance of employees, also with motivational variables positive and significant effect on employee performance. Cultural and motivational variables together (simultaneously), significant positive effect on employee performance front-liner. Based on these results, the implications for the Bank of South Kalimantan is that in supporting organizational culture and motivation also need to pay attention to and improve the quality of potential employees front-liner for example by providing the opportunity to continue the education (like education for services excellent care, education and personality development) and engage in training (like training on banking products, training on risk management, especially with regard to transaction services and risk transaction), so that it can improve employee performance front-liner